TECHNICAL AND TACTICAL ANALYSIS OF MAJOR FOREIGN EPEE OPPONENTS PREPARING FOR THE TOKYO PARALYMPIC GAME IN GROUP B OF THE CHINESE WOMEN’S WHEELCHAIR FENCING TEAM - Kai, He; Lina, Xu; Hongwei, Yan (ASEAN Journal of Sport for Development and Peace, 2022)
This essay analyzes the main scoring methods and technical tactics of the Chinese women's wheelchair fencing team B-level athletes. Preparing for the Tokyo Paralympic Games, the primary foreign epee opponents will provide technical and technical references for the women's wheelchair fencing team support. To summarize the opponent's tactical characteristics and habits and offer concerns and suggestions for the Chinese women's dueling sword wheelchair fencing team, analyze the competition habits and tactics of the main competitors in dueling sword. This essay explores the opponent's main scoring methods by sorting out foreign competitors, the scores of crucial games, and the scores of different parts to be better prepared. Based on the video, the flexible use of technology and tactics can be summarized by searching for relevant information and statistical competition data. The wheelchair fencing team must maintain a solid defensive ability to ensure both offense and defense. In the game, keep good habits and clear thinking, grasp the reality of offensive and defensive conversion, use tactical moves flexibly, combine defensive tactics and tactics, and create good habits for seeking opportunities.